2019
DOI: 10.1055/s-0039-1690770
|View full text |Cite
|
Sign up to set email alerts
|

A Reduction-Sensitive Fluorous Fluorogenic Coumarin

Abstract: Fluorophores that are sensitive to their environment are useful tools for sensing chemical changes and probing biological systems. Here, we extend responsive fluorophores to the fluorous phase with the synthesis of a reduction-sensitive fluorous-soluble fluorogenic coumarin. We demonstrate that this fluorophore responds to various reducing agents, most notably glutathione, a key biological reductant. The fluorous solubility of this probe allows for its encapsulation into two different fluorous nanomaterials: p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
(45 reference statements)
1
6
0
Order By: Relevance
“…To our delight, we observed that 3 considerably increased global tyrosine phosphorylation at 500 μM; however, we observed this increase to also be accompanied by a loss of the β-tubulin and GAPDH housekeeping proteins (Figure c). Additionally, upon using 3 in time-course experiments, we observed the increase in global tyrosine phosphorylation as early as 30 min, consistent with the previously observed rates of similar self-immolative compounds (Figure c,d) . Upon directly comparing 2 , 3 , 6 , and 7 , there was no effect on global phosphorylation observed for either 6 or 7 at 30 min or up to 180 min (Figures e and S3) further bolstering the model of an intracellular BDI being potentially responsible for the observed increase in global tyrosine phosphorylation.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…To our delight, we observed that 3 considerably increased global tyrosine phosphorylation at 500 μM; however, we observed this increase to also be accompanied by a loss of the β-tubulin and GAPDH housekeeping proteins (Figure c). Additionally, upon using 3 in time-course experiments, we observed the increase in global tyrosine phosphorylation as early as 30 min, consistent with the previously observed rates of similar self-immolative compounds (Figure c,d) . Upon directly comparing 2 , 3 , 6 , and 7 , there was no effect on global phosphorylation observed for either 6 or 7 at 30 min or up to 180 min (Figures e and S3) further bolstering the model of an intracellular BDI being potentially responsible for the observed increase in global tyrosine phosphorylation.…”
Section: Resultssupporting
confidence: 88%
“…Upon exposure to the high intracellular concentrations of reducing agents, 25 a direct reduction of the sulfur−sulfur bond is feasible; however, a multistep mechanism is also possible. 29 The resulting thiol is then expected to undergo rapid self-immolative deprotection, as seen in similar compounds, 30 and unmask 2 within the cell. As with the earlier experiments, triazabutadiene 2 is expected to readily release BDI intracellularly (Figure 4a).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The main challenge with PFC nanoemulsions as delivery vehicles is solubilizing payloads in the fluorous phase. We have successfully encapsulated small molecule fluorophores and therapeutics within PFC nanoemulsions through covalent attachment of fluorous tags [14, 16–19] . Recently, Medina and co‐workers extended the payloads capable of being delivered with PFC nanoemulsions to include proteins by creating a “fluorous mask” around GFP with non‐covalent fluorinated anionic tags [20] .…”
Section: Figurementioning
confidence: 99%
“…We have successfully encapsulated small molecule fluorophores and therapeutics within PFC nanoemulsions through covalent attachment of fluorous tags. [14,[16][17][18][19] Recently, Medina and co-workers extended the payloads capable of being delivered with PFC nanoemulsions to include proteins by creating a "fluorous mask" around GFP with non-covalent fluorinated anionic tags. [20] GFP was then delivered in cells using ultrasound-induced cavitation.…”
mentioning
confidence: 99%
“…Coumarins fused to polycyclic systems have received substantial interest from organic, [5][6][7][8][9] medicinal, [10][11][12][13][14] and material chemists for their unique photophysical and photochemical properties. [15][16][17][18][19] Fluorenone (Figure 1) is an example of a polycyclic framework that is widespread in natural products. 20 For instance, the natural products Gramniphenols D and E (Figure 1) exhibit anti-HIV activity.…”
mentioning
confidence: 99%